Projectional Interpretation: Bolesław Prus’s Reading of Zdania i uwagi by Adam Mickiewicz - Ławski, Jarosław (Tematy i Konteksty, 2021)
The article focuses on the interpretation of selected aphorisms of the Romantic poet Adam Mickiewicz (1798–1855) provided by Bolesław Prus (1847–1912), a prose writer and a representative of realism in Polish post-Romantic literature. Prus interpreted religious, sometimes almost mystical, aphorisms as commendation of hard work, activism, and as a manifesto of practical ethics. Inspired by the mystical thoughts of Angelus Silesius, Jakob Böhme and Saint-Martin, Mickiewicz’s aphorisms are perceived as exceptionally ambiguous. Prus, however, projected his own literary and philosophical mindset onto the micro-texts of the Romantic poet and, in consequence, oversimplified their meaning. What he did is here called a projectional interpretation.